2022
DOI: 10.1089/jwh.2021.0493
|View full text |Cite
|
Sign up to set email alerts
|

Financial Instability and Delays in Access to Sexual and Reproductive Health Care Due to COVID-19

Abstract: Objective: To identify prevalence of, and patient and clinic characteristics associated with, delays in access to sexual and reproductive health (SRH) care due to the COVID-19 pandemic across three states with varying COVID-19 context and state government response. Methods: We weighted data collected between May 2020 and May 2021 from monthly and biannual follow-up surveys of patients seeking family planning care at a publicly supported health center in Arizona ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…The current literature on BC access during the pandemic reported challenges with obtaining refills, appointment availability, and affordability, which disproportionately affected minorities and those with financial instability. Our study confirmed emerging data that the pandemic increased worry about BC access [ 9 ] and some BC and reproductive health care access barriers existed [ 9 , 10 , 36 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The current literature on BC access during the pandemic reported challenges with obtaining refills, appointment availability, and affordability, which disproportionately affected minorities and those with financial instability. Our study confirmed emerging data that the pandemic increased worry about BC access [ 9 ] and some BC and reproductive health care access barriers existed [ 9 , 10 , 36 ].…”
Section: Discussionsupporting
confidence: 88%
“…The COVID-19 pandemic has prevented individuals from obtaining necessary reproductive health care [ 8 , 9 , 10 , 11 , 12 ]. Policies and practices enacted in response to the pandemic such as social distancing, stay-at-home orders, and limiting in-person care to “essential” procedures widened gaps in reproductive health access [ 13 ], disproportionately affecting underserved populations [ 8 , 9 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Affluent families also saw increases in the value of their assets as both stock markets and home prices soared (Cian and Rebillard, 2021). At the same time, access to reproductive health care and abortion was disrupted and, in some cases, completely shut down (Kavanaugh, 2022), which may have reduced fertility at older ages while also tending to increase unintended childbirth (Bailey et al, 2022). Also these differences make it important to examine fertility trends by demographic group in order to gain a better understanding of the role of these factors.…”
Section: Introductionmentioning
confidence: 99%
“…While health inequities are a multi‐pronged systemic issue, determining ways to further reduce barriers to telehealth may be particularly important for Black and Latinx individuals, people of color, and people living on low‐incomes who use publicly supported health facilities for their health needs 4,5 . These groups have been more likely to experience delays in accessing SRH services during the pandemic 12 and, due to existing systemic inequities, have been disproportionately affected by COVID‐19 25,28 . Furthermore, telehealth allows increased access to health care for rural, geographically dispersed populations.…”
Section: Discussionmentioning
confidence: 99%